Formulation and Characterization Liposome of Oxcarbazepine - Dina Permata Wijaya; Budi Untari; Herlina Herlina; Putri Siti Rahayu (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Oxcarbazepine (OXC) was used as first line therapy or additional therapy for treatment of partialand secondary of seizures. The penetration of OXC into nasal mucosa can be enhanced by formingliposome. This research has the aim to prepare and characterize iposome laoding OXC. The OXCliposome formula was composed by using soya lechitin and cholesterol with various amount usingthin film hydration method. Characterization by determining the encapsulation efficiency (%EE), pH,viscosity, particle size, polydispersity of index, zeta potential, and in vitro release. The liposome ofOXC was also analyzed for its stability based on heating-coling cycle method. The proportion of bestformula was obtained at the amount of cholesterol of 42,11 mg yield %EE of 92,63%, pH of 8,47,viscosity of 1,10 cP, and decreased amount of OXC in stability test of 0,34%. The results of particlediameter were 579 nm, polydispersity index (PDI) of 0,34, and zeta potential of -99,38 mV. The in vitrorelease of the liposome of OXC was studied and compared with OXC. The result of in vitro releaseliposome OXC (F2) ahowed increase (62,26%) than (41,97%).